Synthesis of chiral hydantoin derivatives by homogeneous Pd-catalyzed asymmetric hydrogenation. Issue 1 (15th January 2017) - Ma, Bao-De; Du, Sheng-Hua; Wang, Yu; Ou, Xiao-Ming; Huang, Ming-Zhi; Wang, Li-Xin; Wang, Xiao-Guang
Graphical abstract: Abstract: 5-Aryl substituted chiral hydantoin derivatives were synthesized via asymmetric hydrogenation of prochiral exocyclic alkenes using a Pd/BINAP catalyst. Moderate to good enantioselectivity were obtained (21–90% ee). A chiral Brönsted acid additive was found to be a key factor to obtain high enantioselectivity. Abstract : 5-Benzylimidazolidine-2, 4-dione: C10 H10 N2 O2 [ α ]D 20 = −36.0 ( c 0.1, TFE) for 46% ee Source of chirality: Asymmetric hydrogenation Absolute configuration: (5 S ) Abstract : 5-(4-Methoxybenzyl)imidazolidine-2, 4-dione: C11 H12 N2 O3 [ α ]D 20 = −27.0 ( c 0.1, TFE) for 63% ee Source of chirality: Asymmetric hydrogenation Absolute configuration: unknown Abstract : 5-(4-Bromobenzyl)imidazolidine-2, 4-dione: C10 H9 BrN2 O2 [ α ]D 20 = −10.0 ( c 0.1, TFE) for 21% ee Source of chirality: Asymmetric hydrogenation Absolute configuration: unknown Abstract : 5-(4-Chlorobenzyl)imidazolidine-2, 4-dione: C10 H9 CIN2 O2 [ α ]D 20 = −50.0 ( c 0.1, TFE) for 26% ee Source of chirality: Asymmetric hydrogenation Absolute configuration: unknown Abstract : 5-(3-Chlorobenzyl)imidazolidine-2, 4-dione: C10 H9 CIN2 O2 [ α ]D 20 = +18.0 ( c 0.1, TFE) for 53% ee Source of chirality: Asymmetric hydrogenation Absolute configuration: unknown Abstract : 5-(2-Chlorobenzyl)imidazolidine-2, 4-dione: C10 H9 CIN2 O2 [ α ]D 20 = −25.0 ( c 0.1, TFE) for 51% ee Source of chirality: Asymmetric hydrogenation Absolute configuration: unknown Abstract : 5-(2-Methoxybenzyl)imidazolidine-2, 4-dione: C11 H12 N2 O3 [ α ]D 20 = −105.0 ( c 0.1, TFE) for 88% ee Source of chirality: Asymmetric hydrogenation Absolute configuration: unknown Abstract : 5-(2-Methylbenzyl)imidazolidine-2, 4-dione: C11 H12 N2 O2 [ α ]D 20 = −125.0 ( c 0.1, TFE) for 90% ee Source of chirality: Asymmetric hydrogenation Absolute configuration: unknown Abstract : 5-(2-Ethoxybenzyl)imidazolidine-2, 4-dione: C12 H14 N2 O3 [ α ]D 20 = −27.0 ( c 0.1, TFE) for 56% ee Source of chirality: Asymmetric hydrogenation Absolute configuration: unknown Abstract : (5-(2-Butoxybenzyl)imidazolidine-2, 4-dione): C14 H16 N2 O3 [ α ]D 20 = −30.0 ( c 0.1, TFE) for 61% ee Source of chirality: Asymmetric hydrogenation Absolute configuration: unknown